Impact of Temporary Voltage Grid Disturbance to Running Speed of Three Phase Induction Motor - Haidar Ali Fathin Naufal; Mochammad Facta; Byan Bagas Pradana; Sidiq Budi Perkasa (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
In the electric power system, especially the distribution system, several disturbances may occur. Voltage grid disturbance is an important power quality problem on the distribution side especially for industry with dynamics loads consisting many three phase electric motors. As the voltage grid disturbance appears, the electrical load especially an induction motor is expected to keep running on the rated speed. This motor condition is also well known as ride-through capability. In this article, the influences of temporary voltage grid disturbances are analysed to know the running speed of an induction motor based on difference in moment of inertia and give further information about the ride through capability by using PSIM simulation as an experimental tool. There are various types of voltage grid disturbance drop will be proposed. The proposed types of voltage grid disturbance to be observed are short duration sag, long duration sag, momentary swell and momentary interruption. The experiential conventional methods observed in the works are direct on line, wye-delta and autotransformer. The PSIM simulation results demonstrate that increasing the rotor moment of inertia from 0.4 to 0.8 enhances the dynamic resilience of the motor by reducing the average speed deviation by approximately 9.76% during a long-duration voltage sag. Meanwhile, the momentary interruption is identified as the most severe grid disturbance, as it leads to a complete loss of electromagnetic torque and consequently causes motor stalling. These findings highlight that the mechanical inertia of the drive system plays a critical role in maintaining motor stability during abnormal supply conditions. Finally, this article provides quantitative evidence on the combined influence of inertia and disturbance severity, offering valuable insight for the optimal design of protection schemes and motor selection criteria in industrial applications.